MODEL PENYELESAIAN CAROK BERDASARKAN CARA BERHUKUM ORANG MADURA - Budimansyah, Budimansyah (TANJUNGPURA LAW JOURNAL, 2018)
Carok is a social reality for the Madurese whose existence is still recognized today. The essence of Carok is more closely related to Madurese cultural values, where Carok is based on the fact that the Madurese have experienced the so-called "Malo", this feeling is caused by the Madurese feeling that their self-esteem is being harassed so as to defend the abused self-esteem then the Madurese do Carok. Law enforcement on Carok can not only be done with a positivistic approach with the nature of rigidity and see that Carok is a black and white subject matter as set forth in the Criminal Code (Criminal Code), if Carok is solved only through criminal law mechanism then no wonder then when the Carok-Carok takes place, the way through the penal law can never touch the nature of Carok, why the Madurese do Carok, and what Carok means and the defense of self-esteem for the Madurese. This research is a normative legal research, the data source used in this study is in the form of secondary data, namely books, journals, legislation, documents and other writings relating to the problem being studied. This study aims to find the law in concreto that is an attempt to find out whether the law that is suitable to be implemented in reality is carried out or obeyed by the community in relation to the settlement of Carok, the data processing method is to use qualitative methods and data analysis is deductive. Based on the results of the study, it is known that the Carok settlement model is based on the way of judging Madurese is different from the settlement model provided by the law of the country where the way of judging Madurese is a cultural approach so that Carok as a problem that comes from culture can be resolved and muted, then the presence of criminal law as the last effort (ultimum remedium) is deemed necessary after it is first settled based on how to enact the Madurese.